INDONESIAN GEOPOLITICS: EXPLORING ROLES ON THE NEW GEOPOLITICAL MAP - Kunkunrat Kunkunrat (Sean Institute, 2023)
In the era of globalization and increasingly complex geopolitical dynamics, a deep understanding of a country's geopolitical position is crucial. This research aims to investigate Indonesia's role in the context of a geopolitical map that continues to change and develop. This research uses a qualitative approach with descriptive methods. The research results show Indonesia's crucial role in global geopolitical dynamics, especially facing changes in the